Prostatic cancer with metastasis to the testis – A case report - Chapagain, U; Neupane, S; Tuladhar, S; Pradhananga, S; Basnet, RB; Regmi, S (Journal of Pathology of Nepal, 2015)
Metastatic carcinoma to the testis is very rare.The incidence of secondary testicular tumors ranges from 0.02 to 2.5% among autopsies ingeneral. Despite the high incidence of prostatic adenocarcinoma and its ability for wide dissemination, metastatic cancer to the testis is a rare phenomenon of prostate carcinoma with only 80 cases reported in the literature.It is diagnosed in autopsies or incidentally, following therapeutic orchiectomies in moreadvanced stages of the disease. Ours is the very first case of prostatic carcinoma metastasizing to the testis, being reported from our country. We are reporting this case because of the rarity of metastasis of prostatic carcinoma to testis and for stressing the need for keeping in mind the possibility of metastatic carcinoma also while dealing with testicular tumors. In our case, unilateral testicular metastasis was detected incidentally after bilateral orchiectomy for hormonal management of metastatic prostatecarcinoma. The metastatic lesion was not identified in physical examination or in macroscopic dissection of the testis after surgery. Microscopy revealed an adenocarcinoma which, given the history of the patient and a positive immunohistochemical stain for PSA, was identified as metastatic prostatic adenocarcinoma. Journal of Pathology of Nepal (2015) Vol. 5, 784-786